Green fluorescent nanomaterials for rapid detection of chromium and iron ions: wool keratin-based carbon quantum dots. Issue 13 (11th March 2022) - Song, Yuanyuan; Qi, Na; Li, Kang; Cheng, Di; Wang, Dong; Li, Ying
Abstract : Synthesis of carbon quantum dots from wool keratin and their potential in detecting chromium and iron ions. Abstract : Heavy metal ions produced by industrial activity have been a serious environmental problem, and their detection is critical for treatment of the heavy metal pollution. Among the variable heavy metal detection methods, fluorescent indicator methods have attracted wide attention due to the advantage of the convenience and nondestructive detection process. Carbon quantum dots have great application in this respect. In this study, nitrogen and sulfur doped fluorescent carbon quantum dots (N, S-CDs) were prepared based on wool keratin using a hydrothermal method, of which the morphology, chemical composition and optical properties were characterized. The prepared N, S-CDs were spherical nanoparticles with a diameter of 2–6 nm, showing wide fluorescence excitation and emission wavelength range and considerable quantum yield, and have sensitive response to Cr 6+ and Fe 3+ . This study reveals a novel cost-effective and convenient synthetic route of green carbon quantum dots through naturally sourced materials, demonstrates the application potential of the wool keratin-based N, S-CDs in rapid detection of heavy metal, and opens up a new path for functional utilization of waste wool keratin.